Management and Outcome of Pediatric Appendicitis in COVID-19 Era - Novia D. Yantika; Harsali Lampus; Angelica M. J. Wagiu (e-CliniC, 2022)
Abstract: The COVID-19 pandemic has an impact on health services including the management of appendicitis in children both infected and infected with COVID-19. Change in the management of appendicitis in children during the COVID-19 pandemic is still controversial regarding the outcomes arising from this management. This study aimed to determine the management and outcome of appendicitis in children infected and uninfected with COVID-19 during the COVID-19 pandemic. This was a literature review study using databases of PubMed, ClinicalKey and Google Scholar and keywords, as follows: (Management paediatric appendicitis and COVID) AND (outcome paediatric appendicitis and COVID). The results obtained 19 articles. There was a modification in the management of pediatric patients with appendicitis during the COVID-19 pandemic, which was an increase in the use of open appendectomy procedures, especially in COVID-19 positive patients and non-operative management, however, some still maintain the laparoscopic procedure. Meanwhile, the outcome of the management showed that there was no significant difference related to the occurrence of complications, the length of stay in patients with surgery, and the high failure rate in patients with non-operative management, therefore, interval appendectomy was needed. In conclusion, there is a modification in the management of appendicitis in children during the COVID-19 pandemic with insignificant outcome in the operative action and failure related to the non-operative management.Keywords: management; outcome; pediatric appendicitis; COVID-19Â Abstrak: Pandemi COVID-19 memberi dampak pada pelayanan kesehatan termasuk manajemen apendisitis pada anak baik yang terinfeksi maupun tidak terinfeksi COVID-19. Perubahan manajemen apendisitis pada anak selama pandemi COVID-19 masih menjadi kontroversial terkait dengan luaran yang terjadi akibat manajemen tersebut. Penelitian ini bertujuan untuk mengetahui manajemen dan luaran apendisitis pada anak yang terinfeksi maupun tidak terinfeksi COVID-19 selama pandemi COVID-19. Penelitian ini berbentuk literature review menggunakan database dari PubMed, ClinicalKey dan Google Scholar dengan kata kunci (Management paediatric appendicitis and COVID) AND (outcome paediatric appendicitis and COVID). Hasil penelitian mendapatkan 19 artikel. Terjadi modifikasi dalam manajemen pasien anak dengan apendisitis selama pandemi COVID-19, yaitu peningkatan dalam penggunaan prosedur apendektomi terbuka terutama pada pasien positif COVID-19 dan manajemen non-operatif, namun beberapa diantaranya tetap memper-tahankan dilakukannya prosedur laparoskopi. Luaran dari manajemen yang dilakukan menunjukkan bahwa tidak didapatkan perbedaan bermakna terkait terjadinya komplikasi, masa rawat inap pada pasien dengan tindakan operatif, dan tingginya tingkat kegagalan pada pasien dengan manajemen non-operatif; oleh karena itu apendektomi interval masih diperlukan. Simpulan penelitian ini ialah adanya modifikasi dalam manajemen apendisitis pada anak selama pandemi COVID-19 dengan luaran yang tidak berbeda bermakna dalam hal tindakan operatif dan kegagalan terkait manajemen non-operatif.Kata kunci: manajemen; luaran; apendisitis pada anak; COVID-19